ELECTROCHEMICAL BEHAVIOR OF XANTHENE FOOD DYE ERYTHROSINE AT GLASSY CARBON ELECTRODE AND ITS ANALYTICAL APPLICATIONS - S Nayak, Deepti; Shetti, Nagaraj P; Katrahalli, Umesha (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Erythrosine is a xanthene food dye used in the food industries to enhance the appearance of the food. The electrochemical behavior of erythrosine at glassy carbon electrode was investigated by cyclic and differential pulse voltammetry. The oxidation peak of erythrosine was observed in phosphate buffer of pH 5.0. The influence of different pH, scan rate and concentration were evaluated. The probable reaction mechanism involved in the oxidation of erythrosine was also proposed. Differential pulse voltammetric method with good precision and accuracy was developed for the determination of erythrosine dye in real samples. The peak currents were found to be linearly dependent on the concentration range of 1 x 10-5 to 6 x 10-4 M. The limit of detection (LOD) and limit of quantification (LOQ) were noticed to be 1.9 x 10-7 and 6.6 x 10-7 M respectively.